2021
DOI: 10.3390/ijms222312668
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Fructose Transporter Gene Slc2a5 Expression by Glucose in Cultured Microglial Cells

Abstract: Microglia play a role in the regulation of metabolism and pathogenesis of obesity. Microglial activity is altered in response to changes in diet and the body’s metabolic state. Solute carrier family 2 member 5 (Slc2a5) that encodes glucose transporter 5 (GLUT5) is a fructose transporter primarily expressed in microglia within the central nervous system. However, little is known about the nutritional regulation of Slc2a5 expression in microglia and its role in the regulation of metabolism. The present study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 61 publications
(91 reference statements)
2
13
1
Order By: Relevance
“…It was reported that microglia are responsive to changes in local glucose levels. For example, microglia alter their morphology and expression levels of inflammatory and activation markers following a change in glucose concentration in a culture medium in vitro [20][21][22][23][24]29]. We found that high concentration of glucose exerts a stimulatory effect on Gdnf mRNA in SIM-A9 cells in the present study.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…It was reported that microglia are responsive to changes in local glucose levels. For example, microglia alter their morphology and expression levels of inflammatory and activation markers following a change in glucose concentration in a culture medium in vitro [20][21][22][23][24]29]. We found that high concentration of glucose exerts a stimulatory effect on Gdnf mRNA in SIM-A9 cells in the present study.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies reported that fructose induces pro-inflammatory response in microglial BV-2 cells, suggesting that a direct action of fructose increases microglial activity [53,54]. Moreover, glucose increases levels of GLUT5-encoding Slc2a5 mRNA in SIM-A9 cells and glucose-induced pro-inflammatory gene expression is attenuated in the presence of GLUT5 inhibitor [29]. These findings raise the possibility that glucose stimulates Gdnf and Manf gene expression through its conversion to fructose.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations